How big data drives green economic development: Evidence from China - Wang, Li; Wu, Yuhan; Huang, Zeyu; Wang, Yanan (Frontiers in Environmental Science, 2022)
With the high-quality economic development of China, this paper investigates the impact of big data on green economic development. In this study, the global MINDW-MML model and a web crawler are used to respectively quantify the level of green economic development and the level of big data. Panel data measurement is then used to test the results empirically based on data from 30 provinces in China from 2011 to 2018. According to the study, big data promotes green economic development, and it advances technological progress more than it improves efficiency. The analysis of big data sub-indicators shows that cloud computing, Internet of Things, artificial intelligence, and Hadoop positively impacts technological progress, while blockchain positively affects efficiency. Further research reveals that the role of big data in promoting technology is more apparent in the central and eastern regions, and provinces that have strong environmental governance and have developed digital inclusive finance. As moving into the good phase of the economy, big data is more inclined to enhance technological progress, while in a sluggish phase, it improves efficiency more.